Model Pemberdayaan Masyarakat Berkelanjutan pada Sektor Perkebunan Kelapa di Kabupaten Asahan - Ahmed Fernanda Desky; Nabila Yasmin; Mhd. Reza Ardillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
People's coconut commodities have a strategic role for the economy of coastal communities, but their development is still faced with structural, institutional, and low technology utilization. This study aims to analyze the practice of social engineering in sustainable empowerment in the coconut farming community in Asahan Regency by examining the structure-agency relationship that affects the sustainability of the business and the welfare of farmer families from the upstream to downstream sectors. The research uses a qualitative approach with case study methods in Silau Lama Village, Silo Bonto Village, and Central Sei Kepayang Village. The research informants consisted of six people, including coconut farmers, value chain actors, and village government members, who were selected through purposive sampling. Data was collected through observation, in-depth interviews, and documentation studies, then analyzed interactively through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that coconut cultivation practices are still dominated by traditional knowledge, minimal replanting, and weak farmer institutions, so that the productivity and bargaining position of farmers are low. In the downstream sector, the coconut value chain is informal and hierarchical with a high dependence on agents and fluctuations in market prices. Structure-agency relationships show that farmers tend to reproduce old practices as survival strategies due to limited policy and institutional support. This research provides theoretical benefit in enriching the study of rural sociology regarding social engineering and structure-agency relations in farming communities, as well as practical benefits as a reference for the formulation of policies to strengthen institutions and downstream people's coconuts. This study recommends the formation of farmer collective institutions, replanting based on mutual cooperation, sustainable mentoring, and the development of integrated upstream-downstream coconuts to improve the welfare of farmers in a sustainable manner.